Mapping sponsorship portfolios in esports: implied strategic continuity and diversification in the league of legends pro league - Zhu, Pengyu; Agudamu; Zhao, Siyuan; Zhang, Yang (Frontiers in Sports and Active Living, 2025)
ObjectiveAlthough corporate sponsorship is the primary controllable revenue stream in professional esports, its strategic management—particularly regarding continuity and diversification—remains largely under-theorized. This gap is notable given the volatility and rapid commercialization of top-tier leagues. Focusing on China's League of Legends Pro League, this study examines how sponsorship portfolios are structured and sustained over time.MethodsUsing 2021–2024 data from 17 clubs and the league, sponsorship continuity was quantified via Jaccard similarity coefficients and diversification via Blau indices across 25 MSCI industry categories.ResultsTencent-managed league-level portfolios were both stable and diversified, while most club portfolios were volatile and concentrated. Publicly held clubs achieved significantly greater diversification than private clubs, reflecting governance advantages. Club performance predicted greater subsequent diversification but not continuity. Positioning clubs within a continuity–diversification matrix revealed only a few in the “Strategic Resilience” quadrant, with many “At Risk.”ConclusionThese findings suggest that clubs should prioritize a core set of enduring sponsors while expanding into diverse categories to reduce revenue volatility, strengthen bargaining power, and enhance resilience to market shocks. The study provides a replicable framework for evaluating sponsorship continuity and diversification, supporting evidence-based decision-making in esports managerial practice.